The role of CITES Rescue Centers in orchid conservation: concerns and questions raised by the collaboration on an endangered slipper orchid (Paphiopedilum vietnamense O. Gruss & Perner) - Mirenda, Thomas; Wallick, Kyle; Gabel, Robert (Lankesteriana: International Journal on Orchidology, 2015)
The Convention on the International Trade in Endangered Species (CITES) is an international treaty currently adopted by 169 member countries to regulate international trade in over 30,000 species of animal and plants. Plants that are not transported in accordance with CITES requirements may be either denied entry, and sometimes abandoned, or subject to seizure by enforcement officials in importing coun- tries. Instead of being destroyed, abandoned or con- fiscated plants may be returned to the range countries or sent to CITES Rescue Centers, which are public museums or botanical gardens in member countries where the plants are cared for and cultivated.